Institutional Self-Assessment Tool, Version 2 (ISAT2) - Jhangiani, Rajiv; Pakkal, Oya; Lachaîne, Catherine; Luke, Robert (Université d'Ottawa | University of Ottawa, 2024)
Survey instrument that may be used by post-secondary institutions to self-assess their capacity to support open educational practices (OEP) as well as the maturity of their OEP initiatives.
Keywords: open educational practices, postsecondary, Open educational resource (OER)